2017
DOI: 10.3390/s17112468
|View full text |Cite
|
Sign up to set email alerts
|

Trail-Based Search for Efficient Event Report to Mobile Actors in Wireless Sensor and Actor Networks

Abstract: In wireless sensor and actor networks, when an event is detected, the sensor node needs to transmit an event report to inform the actor. Since the actor moves in the network to execute missions, its location is always unavailable to the sensor nodes. A popular solution is the search strategy that can forward the data to a node without its location information. However, most existing works have not considered the mobility of the node, and thus generate significant energy consumption or transmission delay. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…It should be pointed out that reducing the number of actuator updates may be preferable for some practical applications where some embedded processors with limited resources are employed [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Clearly, the above finite-time consensus control schemes need to continuously update control signals and cannot provide any support for this case.…”
Section: Related Workmentioning
confidence: 99%
“…It should be pointed out that reducing the number of actuator updates may be preferable for some practical applications where some embedded processors with limited resources are employed [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Clearly, the above finite-time consensus control schemes need to continuously update control signals and cannot provide any support for this case.…”
Section: Related Workmentioning
confidence: 99%
“…Two different event conditions for fault-tolerant control are studied in [23] in terms of the system state and the system state error, respectively. A great deal of research progress has been made (see [24][25][26][27][28][29][30] and the references therein). It was shown in [31] that the deception attacks are viewed as the most dangerous attack behaviors and, therefore, some solutions against deception attacks have been proposed.…”
Section: Related Workmentioning
confidence: 99%
“…The work in [28] proposed optimal and suboptimal consensus filters with event-triggered communication protocols to achieve energy efficiency via reducing unnecessary interactions among the neighboring sensors. More related studies can be found in recent publications [31,32,33,34,35,36,37,38,39,40,41] and references therein.…”
Section: Introductionmentioning
confidence: 99%